2016
DOI: 10.1007/978-1-4939-6707-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Species and Their Associated Mycotoxins

Abstract: The genus Aspergillus is among the most abundant and widely distributed organism on earth, and at the moment comprises 339 known species. It is one of the most important economically fungal genus and the biotechnological use of Aspergillus species is related to production of soy sauce, of different hydrolytic enzymes (amylases, lipases) and organic acid (citric acid, gluconic acid), as well as biologically active metabolites such as lovastatin. Although they are not considered to be major cause of plant diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 47 publications
2
44
0
8
Order By: Relevance
“…Aflatoxin B1 (AFB1), which is a toxin produced by the fungi Aspergillus flavus and Aspergillus parasiticus , 1 has been extensively studied for its hepatotoxic and carcinogenic properties. 2 – 4 AFB1 is classified as a Group I carcinogen by the International Agency for Research on Cancer ( http://monographs.iarc.fr/ENG/Monographs/vol56/mono56.pdf ).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin B1 (AFB1), which is a toxin produced by the fungi Aspergillus flavus and Aspergillus parasiticus , 1 has been extensively studied for its hepatotoxic and carcinogenic properties. 2 – 4 AFB1 is classified as a Group I carcinogen by the International Agency for Research on Cancer ( http://monographs.iarc.fr/ENG/Monographs/vol56/mono56.pdf ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common and known one is fumonisin B1. Fumonisin B1 is synthesized by F. verticillioide, F. proliferatum ve F. nygami (42,45). However, due to its absorption and kinetics properties, it is reported that meat and meat products are not important sources for public health (11).…”
Section: Fumonisinsmentioning
confidence: 99%
“…It is classified as a saprophyte fungus, but it can also colonize plant tissues, so it could be also considered as an opportunistic plant pathogen. Furthermore due to its ability to produce aflatoxins its presence in foodstuff can be quite dangerous (Perrone and Gallo, 2017). So, the spoiled crops and stored grains by A. flavus have a very high impact on both health and economy (Bhatnagar-Mathur et al, 2015).…”
Section: Introductionmentioning
confidence: 99%